A Political Memoir of the Anglo-French Condominium of the New Hebrides - Woodward, Keith (ANU Press, 2014)
Keith Woodward has produced an inside account of the intricacies of official politics in the latter stages of the history of the Anglo-French Condominium of the New Hebrides, which will be essential reading for anyone interested in the colonial period of Vanuatu.